2021
DOI: 10.1038/s41380-021-01291-y
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate exercise level attenuates gut dysbiosis and valeric acid increase to improve neuroplasticity and cognitive function after surgery in mice

Abstract: Postoperative cognitive dysfunction (POCD) affects the outcome of millions of patients each year. Aging is a risk factor for POCD. Here, we showed that surgery induced learning and memory dysfunction in adult mice. Transplantation of feces from surgery mice but not from control mice led to learning and memory impairment in non-surgery mice. Low intensity exercise improved learning and memory in surgery mice. Exercise attenuated surgery-induced neuroinflammation and decrease of gut microbiota diversity. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 55 publications
(94 reference statements)
5
81
0
Order By: Relevance
“…Our previous study has shown that surgery increases HDAC activity and reduced brain‐derived neurotrophic factor in the hippocampus 7 . Our most recent study has shown that surgery decreases postsynaptic density protein 95 and synapsin 1, two synaptic proteins, and preoperative exercise attenuates this decrease 38 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our previous study has shown that surgery increases HDAC activity and reduced brain‐derived neurotrophic factor in the hippocampus 7 . Our most recent study has shown that surgery decreases postsynaptic density protein 95 and synapsin 1, two synaptic proteins, and preoperative exercise attenuates this decrease 38 …”
Section: Discussionmentioning
confidence: 96%
“…7 Our most recent study has shown that surgery decreases postsynaptic density protein 95 and synapsin 1, two synaptic proteins, and preoperative exercise attenuates this decrease. 38 Thus, surgery can reduce multiple proteins in addition to neuroligin 1. These affected proteins include other synaptic proteins, such as synapsin 1 and postsynaptic density 95.…”
Section: Discussionmentioning
confidence: 99%
“…These pathological mechanisms could be ameliorated by the increase of beneficial bacteria in the gut, such as Bifidobacterium , Lactobacillus , and Galactose oligosaccharide ( Jeong et al, 2015 ; Kobayashi et al, 2017 ; Yang et al, 2018 ). Furthermore, the latest research has shown that proper exercise improved postoperative neuroplasticity and cognitive function by ameliorating the gut dysbiosis and valeric acid increase ( Lai et al, 2021 ). However, it is still unclear how the gut microbiota and neurons in the brain mutually interacted and how these interactions affected normal brain cognitive function ( Chen et al, 2021 ).…”
Section: Potential Mechanisms Of Central Neuroinflammation Occurrencementioning
confidence: 99%
“…Comprehensive behavioral and neurophysiological studies in preclinical animal models are essential to understand the effect of preoperative interventions on the pathophysiology of PND [16]. Preoperative exercise and enriched environment have been shown to attenuate postoperative cognitive impairment in multiple aged rodent studies [81][82][83][84]. Both exercise and enriched environment appear to prevent neuroinflammation in these animal models [82,84].…”
Section: Preclinical Studiesmentioning
confidence: 99%